High prevalence of cough and common cold medication intoxications in the Czech paediatric population - Konopásek, Patrik; Kotíková, Kateřina; Pecková, Monika; David, Jan (Klinische Pädiatrie, 2025)
There has been much debate about the appropriateness of over-the-counter (OTC) cough and common cold medications (CCM). The aim of this nationwide study was to analyse the incidence of CCM intoxications in the Czech paediatric population from 2014 to 2023.We performed a retrospective study on the incidence of CCM intoxications in the Czech paediatric population (ages 0–18 years) from 2014 to 2023.There were 7,056 cases of CCM intoxication in children, of which 6,406 resulted from unintentional intoxication. No lethal doses were reported, but there were 1,769 documented toxic doses. Unintentional CCM intoxications represented 15.60% of all unintentional medication intoxication cases across all ages and medication types. Of the 6,406 unintentional intoxication cases, 5,465 (85.31%) were in children aged 0 to 6 years, including 1,564 (24.41%) in children aged 0 to 2 years. Children aged 0 to 6 years had a significantly higher risk of CCM intoxication compared to those aged 7 to 18 years (RR 9.5, p<0.00001). The annual incidence of unintentional CCM intoxication was 69.26 per 100,000 children aged 0 to 6 years and 7.29 per 100,000 children aged 7 to 18 years.Based on our data, we believe there is low awareness among parents and Czech paediatricians regarding the potential risks of CCM and the lack of proven efficacy of these medications.Our data may contribute to political discussions regarding the general prohibition of CCM use in children younger than six years.
Keywords: children; upper respiratory infections; cough; common cold; intoxication